2020
DOI: 10.3389/fimmu.2020.01654
|View full text |Cite
|
Sign up to set email alerts
|

Altered Microbiota, Impaired Quality of Life, Malabsorption, Infection, and Inflammation in CVID Patients With Diarrhoea

Abstract: Background: Diarrhoea is the commonest gastrointestinal symptom in patients with common variable immunodeficiency (CVID). Objective: The aim of this study was to describe the prevalence and clinical presentation of chronic and recurrent diarrhoea in the Royal-Free-Hospital (RFH) London CVID cohort, including symptoms, infections, level of inflammation, and microbial diversity. Methods: A cross-sectional study of adult CVID patients (139 out of 172 diagnosed with CVID completed the screening questionnaire). Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
(87 reference statements)
1
18
0
Order By: Relevance
“…The limited size of samples is a result of the relatively low prevalence and underdiagnosis of CVID in the population and also of the study inclusion and exclusion criteria, however, size of the cohort is comparable to other CVID microbiome studies. Since previous studies showed that the microbiome of CVID patients is affected by the disease diagnosis, disease severity (11,13), and also by sharing the same household (13,14), we have selected paired samples that could minimize the effect of environment and diet, together with selection of CVID patients without gastroenterological symptomatology for minimization of the impact of CVID complications and treatment regiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited size of samples is a result of the relatively low prevalence and underdiagnosis of CVID in the population and also of the study inclusion and exclusion criteria, however, size of the cohort is comparable to other CVID microbiome studies. Since previous studies showed that the microbiome of CVID patients is affected by the disease diagnosis, disease severity (11,13), and also by sharing the same household (13,14), we have selected paired samples that could minimize the effect of environment and diet, together with selection of CVID patients without gastroenterological symptomatology for minimization of the impact of CVID complications and treatment regiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the effect of diagnosis on bacterial composition was lower than the effect of the environment and nutrition suggesting that the microbial composition is impacted by several additional factors and highlighting the importance of picking the closest control possible. Recently, two studies used matched housemates as controls for CVID and both observed significant effect of household (13,14).…”
Section: Cvid Microbiota Shows Subtle Differences On a Species Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings also support the concept that there is not a single universal healthy gut microbiota composition. Host lifestyle factors, genetic background, health or specific diseases, the environment as well as aging drive microbiota composition and may result in several shifts and alterations over time [49][50][51]. For example, we discovered a modest but significant impact of age and genetic type of CGD (X-linked versus autosomal recessive) on beta diversity in our cohort.…”
Section: Discussionmentioning
confidence: 74%
“…The molecular pathways by which gut microbiota contribute to systemic inflammation in patients with CVID are of great importance but remain poorly understood. CVID patients may have increased intestinal permeability caused by a variety of direct and indirect microbial and immunological mechanisms associated to CVID-related enteropathy ( 44 , 48 , 63 ). This condition provides an impairment of the gut barrier, predominantly caused by disruption of intercellular tight junctions.…”
Section: Gut Microbiota In Cvidmentioning
confidence: 99%